Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Coprecipitation technique to prepare LiTaO3 powders - Navale, SC; Gaikwad, A. B.; Ravi, V (Materials Letters, 2006)
A simple coprecipitation technique had been successfully applied for the preparation of pure ultrafine single phase LiTaO3 (LT). An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Li+ and Ta5+ cations as carbonate and hydroxide respectively. This precursor oil heating at 750 degrees C produces LT powders. For comparison, LT powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Coprecipitation technique to prepare NaNbO3 and NaTaO3 - Samuel, V; Gaikwad, A. B.; Ravi, V (Bulletin of Materials Science, 2006)
A simple coprecipitation technique has been used successfully for the preparation of pure, ultrafine, single phases of NaNbO3 (NN) and NaTaO3 (NT). An alcoholic solution of ammonium carbonate and ammonium hydroxide was used to precipitate Na+ and Nb5+ (or Ta5+) cations under basic conditions as carbonate and hydroxide, respectively. On heating at 700 degrees C, these precursors produce respective products. For comparison, both NN and NT powders were also prepared by the traditional solid state method. The phase purity and lattice parameters were studied by powder X-ray diffraction (XRD). The particle size and morphology were studied by scanning electron microscopy (SEM).
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Coprecipitation technique to prepare CoTa2O6 and CoNb2O6 - Mulla, Imtiaz S.; Natarajan, N.; Gaikwad, A. B.; Samuel, V.; Guptha, U. N.; Ravi, V. (Materials Letter, 2007)
An aqueous solution of sodium hydroxide was used to coprecipitate cobalt and tantalum (or niobium) ions from their precursors as hydroxides under basic conditions. This precipitate yielded CoTa2O6 (CT) or CoNb2O6 (CN) ceramics on calcining at 700 degrees C, i.e. at a temperature much lower than 900 degrees C, reported for the formation of these powders prepared by the traditional solid state method. The X-ray diffraction (XRD) studies were employed to investigate phase contents and lattice parameters. The morphology of the synthesized powders was investigated by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare NiNb2O6 - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Natarajan, N.; Ravi, V. (Materials Letter, 2007)
A mixture of ammonium carbonate and ammonium hydroxide was used to coprecipitate nickel and niobium ions as nickel carbonate and niobium hydroxide under basic conditions. This precursor yielded NiNb2O6 (NN) ceramics on calcining at 700 degrees C (at a temperature lower than 800 degrees C which is necessary for the formation of NiNb2O6 when prepared by the traditional solid state method). The average particle size and morphology of these powders were investigated by transmission electron microscope (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)